2012
DOI: 10.1124/dmd.112.047613
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and Metabolism of LY2452473, a Selective Androgen Receptor Modulator, in Humans

Abstract: ABSTRACT:The disposition and metabolism of isopropyl N-[(2S)-7-cyano-4-(2-pyridylmethyl)-2,3-dihydro-1H-cyclopenta[b]indol-2-yl]carbamate (LY2452473; a selective androgen receptor modulator) in humans was characterized after a single 15-mg (100 Ci) oral dose of [ 14 C]LY2452473 to six healthy male subjects. LY2452473 was absorbed rapidly (time to reach maximum plasma concentration for both LY2452473 and total radioactivity was 2-3 h) and cleared slowly (plasma terminal t 1/2 of 27 h for LY2452473 and 51 h for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…Subsequently, the ratio of reagents 1 a and 2 a was modified, but no further improvement in the yield was obtained (entries 9-11). Moreover, the effect of catalyst loading on the reaction was investigated (entries [12][13][14], which revealed that 5 mol % of 4 d could catalyze the reaction just as well as 10 mol % of 4 d (entry 12 versus entry 1), but that increasing the catalyst loading could improve the yield and the enantioselectivity (entries 13 and 14 versus entry 1). Finally, a catalyst loading of 15 mol % 4 d was regarded as optimal for its good performance in raising the yield to 68 % with a retained excellent stereoselectivity of > 95:5 d.r.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the ratio of reagents 1 a and 2 a was modified, but no further improvement in the yield was obtained (entries 9-11). Moreover, the effect of catalyst loading on the reaction was investigated (entries [12][13][14], which revealed that 5 mol % of 4 d could catalyze the reaction just as well as 10 mol % of 4 d (entry 12 versus entry 1), but that increasing the catalyst loading could improve the yield and the enantioselectivity (entries 13 and 14 versus entry 1). Finally, a catalyst loading of 15 mol % 4 d was regarded as optimal for its good performance in raising the yield to 68 % with a retained excellent stereoselectivity of > 95:5 d.r.…”
Section: Resultsmentioning
confidence: 99%
“…This structure is also present in many natural alkaloids and bioactive molecules. [12] Herein, we report the first catalytic asymmetric cascade reactions of 7-vinylindoles, which have been accomplished through the rational design of such substrates. Such cascade reactions with 3-indolylmethanols in the presence of a chiral phosphoric acid allow the diastereo-and enantioselective synthesis of C7functionalized indoles as well as the construction of cyclopen-ta[b]indole and spirooxindole frameworks (all > 95:5 d.r., 94-> 99 % ee).…”
Section: Introductionmentioning
confidence: 99%
“…1) [25,[32][33][34][35][36], clinical efficacy data have only been reported for LGD-4033 (Ligand Pharmaceuticals, one Phase I trial), MK-0773 (Merck & Co., one Phase II trial), and enobosarm (GTx, Inc., one Phase I and two Phase II trials). 1) [25,[32][33][34][35][36], clinical efficacy data have only been reported for LGD-4033 (Ligand Pharmaceuticals, one Phase I trial), MK-0773 (Merck & Co., one Phase II trial), and enobosarm (GTx, Inc., one Phase I and two Phase II trials).…”
Section: Clinical Trials With Selective Androgen Receptor Modulatorsmentioning
confidence: 99%
“…[7] While in Europe, growth promoters have been banned for use in food-producing animals since 1988 (Council Directive 88/146/EEC prohibiting the use livestock farming of certain substances having a hormonal action 1988), strategies to detect potential SARMs misuse in livestock production are urgently required to guarantee consumers of food from animal origin free of any residues of such compounds. Furthermore, and because it has been demonstrated in different species that SARMs were eliminated in the faeces, [9,[22][23][24][25][26][27][28][29][30] the present work aims at studying faeces as an alternative interesting biological matrix to detect these substances in livestock. [18,19] Since these compounds have recently emerged, they have not been investigated a lot.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore propose in this study to investigate further SARMs elimination and metabolism in bovine. Furthermore, and because it has been demonstrated in different species that SARMs were eliminated in the faeces, [9,[22][23][24][25][26][27][28][29][30] the present work aims at studying faeces as an alternative interesting biological matrix to detect these substances in livestock. Faeces is indeed an easy-to-collect matrix and its relevance in livestock for detecting some residues or metabolites of growth promoters has already been demonstrated.…”
Section: Introductionmentioning
confidence: 99%